Natural hosts of SIV : implication in AIDS - Ansari, Aftab A. (Aftab Ahmed); Silvestri, Guido (Professor of pathology and laboratory medicine) (Academic Press is an imprint of Elsevier, 2014)
Natural Hosts of SIV: Implications in AIDS thoroughly reviews the possible mechanisms by which African nonhuman primate natural hosts of lentiviruses remain essentially disease-free while other hosts exhibit disease and death. The book ultimately indicates directions for further research and potential translations of this compelling phenomenon into novel approaches to treat and prevent HIV. When Asian non-human primate non-natural hosts are experimentally infected with viruses isolated from African species, disease and death normally results. Meanwhile, these African nonhuman primate natural hosts maintain similar levels of plasma and cellular viremia and exhibit compellingly different, essentially disease-free, states. This work attempts to answer the question of how the natural host remains disease resistant.